Effect of gas pressure on the microstructure of parts foamed with the novel microcellular injection molding technology Ku‐Fizz™. (26th May 2021) - Simon, Sara Andrea; Hain, Jörg; Osswald, Tim
Abstract: The increasing demand for lightweight and economical automotive components boosts investigation of advanced materials and new lightweighting technologies. This work employs the novel microcellular injection molding technology Ku‐Fizz™. The process introduces gas with granulates at moderate low pressures into the feed zone of the injection molding machine. Ku‐Fizz is controlled by gas pressure; thus, a simple plate geometry was molded and the effect of various gas contents on the microstructure was analyzed. The material used was a chemically coupled glass fiber‐reinforced polypropylene compound. Optical microscopy was employed to measure the foam microstructure. Microcomputed tomography was used to quantify the fiber volume fraction and the orientation tensors. Results of the fully characterized microstructure showed cell density increasing and cell size decreasing with gas pressure and melt flow direction. Fiber length increased with gas content. Cell growth displaced fibers from the center of the part towards the mold surface, changing the fiber concentration and global fiber orientation. Abstract :